Service Innovation of the E-Peken Application (Economic Empowerment and Resilience) by the Department of Communication and Informatics of Surabaya City - Rania Hari Andari; Trenda Aktiva Oktariyanda; Tjitjik Rahaju; Galih Wahyu Pradana (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
The role and concern of the government are essential to support the success of e-commerce activities. One way is by innovating services in applications in terms of economic empowerment and resilience. Surabaya City is one of the cities with technology-based innovations that excels E-PEKEN as a mobile-based application that connects MSMEs with consumers. However, the application, which launched on October 31, 2021, still requires further development and refinement to achieve its stated objectives. Therefore, the government hopes that this new application innovation will prompt a swift public response and feedback regarding the advantages and benefits of the E-PEKEN application. This study aims to analyze and describe the service innovation of the E-PEKEN application (Economic Empowerment and Resilience) by the Surabaya City Communication and Informatics Office. This study uses a qualitative research type with a descriptive method, with data collection techniques using observation techniques, structured interviews, and documentation. The results of the study indicate that the E-PEKEN Surabaya service innovation (Economic Empowerment and Resilience in Surabaya) by the Surabaya City Communication and Informatics Office can be said to be good because it has met all the criteria and characteristics of existing innovations. The E-PEKEN Surabaya service has uniqueness or specificity, proven in terms of ideas, programs, structures, systems, and possible expected results, which are different from before. Furthermore, this service has an element of novelty, as it is an original innovation, truly an idea and a work of thought from members of the Surabaya City Communication and Informatics Office. Â